Knowledge, attitudes, practices and perceived barriers of evidence-based practice among Registered Nurses in a Ghanaian Teaching Hospital - Confidence Alorse Atakro; Abigail Atakro; Cynthia Pomaa Akuoko; Janet Sintim Aboagye; Alice Aluwah Blay; Stella Boatemaa Addo; Peter Adatara; Dorcas Frempomaa Agyare; Kwaku Gyimah Amoa-Gyarteng; Isabella Garti; Awube Menlah; Isaac Kwadwo Ansong; et al. (Elsevier, 2020)
Objective: This study aimed at investigating knowledge, attitudes, practices and perceived barriers of evidence-based practice among Registered Nurses in a Ghanaian Teaching Hospital. Methods: The study utilised mixed methods. Self-completion questionnaire and individual semi-structured interviews were used in collecting data. One hundred and two nurses were involved in survey whilst twenty nurses were interviewed. Survey data were analysed with SPSS version 20 whilst qualitative data were analysed through content analysis to generate categories. Results: The response rate in this study was 68%. Almost all participants (91.2%) were below the age of 35. Majority of Registered Nurses demonstrated a generally high levels of knowledge, attitude and practice of EBP. However, almost half of participating nurses (47.7%) thought that their workload was too high to keep up to date with current evidence. Qualitative results identified training, institutional and nursing job related barriers that impeded full implementation of evidence-based practice among registered nurses within the teaching hospital setting in Ghana. Conclusion: This study identified areas that need improving in order to have nurses fully practice evidence-based practice within Ghanaian hospitals. Managers of Ghanaian hospitals should take steps to provide resources needed for evidence-based practice and collaborate with academia in addressing training related barriers of evidence-based practice noted by nurses.